Prioritizing the Factors Affecting the Abuse of Pharmaceutical Opioids by Applying Topsis: Factors Affecting the Abuse of Pharmaceutical Opioids - Farahnaz Zeinali,; Mehdi Mohammadzadeh,; Jamshid Salamzadeh, (Iranian Journal of Pharmaceutical Sciences, 2018)
Human societies have witnessed the phenomenon of ever-increasing use of pharmaceutical opioids for a long time. Moreover, cultural, social, and economic aspects in any community have undergone the negative effects of the growing tendency toward opioids addiction. Since abusing pharmaceutical opioids is a serious problem, it is important to recognize and prioritize the factors influencing this abuse. This paper concentrates on assessing the priorities of variables which have effects on the abuse of pharmaceutical opioids in order to help the policy makers to make correct decisions to reduce the abuse of opioids.Topsis is applied as a method for Multi-Attribute decision making, which prioritizes alternatives in a simple but efficient way. Topsis method identifies the closeness of each alternative to the ideal solution. In this method, each alternative should have the shortest distance from the best solution and the farthest distance from the worst solution. According to the findings, ―family role‖ and ―extra prescription‖ are the most important factors in variables.